Blood, sweat, & tears Jake Gaither, Florida A&M, and the history of Black college football - White, Derrick E. (University of North Carolina Press, 2019)
"Blood, sweat, and tears explores the legacy of black college football, taking as its central figure one of the most successful coaches in its history, Jake Gaither. A paradoxical figure, he was leader of the most feared and respected black college football program in the country, and yet many questioned his racial loyalties during the height of the civil rights movement ... a ... story of black college football that complicates the heroic narrative of integration and grapples with the complexities and contradictions of one of the most important sources of pride of black life in the twentieth century"--
Keywords: Gaither, Jake / 1903-1994; Florida Agricultural and Mechanical University; Florida Agricultural and Mechanical University / Football; Geschichte 1900-1999; Football coaches / United States / Biography; African American universities and colleges / Sports; Football / Social aspects / United States; College sports / United States / History / 20th century; American Football; Hochschulsport; USA